Fatores associados ao tempo sentado de idosos residentes nos municípios da Superintendência Regional de Saúde de Uberaba/Minas Gerais - MENEGUCI, Joilson (2014)
Front the evidences demonstrated in the literature, assessment of sedentary behavior in elderly has become a growing concern and of paramount importance for the public healthcare. Since, in addition to the significant increase in the number of elderly, this population tend to spend more time of the day in sedentary behavior. Thus, the aims of this study were to ascertain the association between the longer sitting time of the elderly with their socio-demographic, clinical, and habitual profile and research the association between sitting time and quality of life of elderly. A Cross-Sectional study was conducted in twenty-four municipalities located in the Triângulo Mineiro region, Minas Gerais, Brazil, based on a population of 79,924 aged 60 years old or older. Eligible participants completed a structured questionnaire, containing sociodemographic information, clinical, habits and quality of life, and underwent assessment of body mass and height. The overall sitting time was evaluated according to the self-report of time spent seated on a usual weekday and a usual weekend day and the quality of life was assessed by the instruments WHOQOL-BREF and WHOQOL-OLD. A Multiple Correspondence Factor Analysis showed that the greatest sitting time was associated with women, ≥70 years old, unschooled, suffering from arterial hypertension and/or diabetes mellitus, who use medication, have poor self-rated health, are dependent on others to perform the basic activities of daily living, and who do not have regular physical activity. The association between sitting time and quality of life, performed by logistic regression analysis, indicated that were associated with sitting time, ≥ 334.28 minutes/day the score ≤ 53,57 of domain Physical (OR=1.807; 95% CI: 1.396 – 2.341) and score ≤ 62.50 for facet of social participation (OR=1.425; 95% CI: 1.102 – 1.843). According to the results of this study, the longest sitting time by the elderly persons evaluated was associated with the socio-demographic profile: female, age ≥ 70 years old, and unschooled; clinical profile: arterial hypertension, diabetes mellitus, use of medication, poor self-rated health, and dependent on others to perform the basic activities of daily living; and habits: does not have regular physical activity. In relation to quality of life, the worst scores for the domain physical and facet social participation were associated with longer sitting time.